Exclusive Enteral Nutrition Plus Immediate vs. Delayed Washed Microbiota Transplantation in Crohn's Disease With Malnutrition: A Randomized Pilot Study - Xiang, Liyuan; Yu, Yan; Ding, Xiao; Zhang, Hui; Wen, Quan; Cui, Bota; Zhang, Faming (Frontiers in Medicine, 2021)
Background: The potential of washed microbiota transplantation (WMT) in Crohn's disease (CD) has been reported. This study aimed to explore the suitable timing of WMT in patients with CD complicated with malnutrition. Methods: This is a randomized, open-label study. Patients with active CD complicated with malnutrition were included and 1:1 randomized to undergo WMT at day 1 (group WMT-DAY1) or day 8 (group WMT-DAY8). The observation duration was 15 days. Exclusive enteral nutrition (EEN) was administered in both groups. The primary outcome was the improvement in nutritional parameters at day 8 and day 15 in two groups. The secondary outcome was the rate of clinical remission at day 15 in two groups. Results: Totally 19 patients completed the trial. At day 8, the lymphocyte count, albumin and prealbumin increased significantly compared to those at day 1 in group WMT-DAY1 (p = 0.018, p = 0.028, p = 0.028, respectively), while no significant increase in any nutritional parameter was shown in group WMT-DAY8. At day 15, albumin increased significantly compared to that at day 1 in both groups (p < 0.05), while significant increase in prealbumin was only shown in group WMT-DAY1 (p = 0.004) compared to that at day 1. The rate of clinical remission at day 15 in group WMT-DAY1 and group WMT-DAY8 was 87.5% (7/8) and 72.7% (8/11), respectively (p = 0.603). Conclusion: EEN combined with immediate WMT intervention could rapidly improve the nutritional status and induce clinical remission in malnourished patients with CD. Clinical Trial Registration:www.ClinicalTrials.gov, identifier: NCT02897661.